Finance and Development, September 1964. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1964)
This paper discusses events related to creation of the IMF. The paper highlights that representatives of 45 countries met at Bretton Woods, New Hampshire, a summer resort in the northeastern part of the United States, to prepare the final texts of the Articles of Agreement of the IMF and of the International Bank for Reconstruction and Development. The paper also discusses activities of the IMF in Latin America, highlighting that the Latin American countries offer a rich variety of economic experience, ranging from examples of financial stability and sustained economic growth to chronic difficulty or acute crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet